2015
DOI: 10.1016/j.str.2015.09.015
|View full text |Cite
|
Sign up to set email alerts
|

The High-Resolution Structure of Activated Opsin Reveals a Conserved Solvent Network in the Transmembrane Region Essential for Activation

Abstract: Rhodopsin, a light-activated G protein coupled receptor (GPCR), has been the subject of numerous biochemical and structural investigations, serving as a model receptor for GPCRs and their activation. Herein we present the 2.3 Å resolution structure of native-source rhodopsin stabilized in a conformation competent for G protein binding. An extensive water-mediated hydrogen bond network linking the chromophore binding site to the site of G protein binding is observed, providing connections to conserved motifs es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 51 publications
(53 reference statements)
3
31
0
Order By: Relevance
“…The path of ACKR3 residues with agonist-induced increases in oxidation rates is in striking agreement with solvent networks identified in active states of both rhodopsin and opioid receptors (Fig. 8b)4143. Previous radiolytic footprinting studies of GPCRs have shown that higher oxidation rates of residues lining this path correlate with an increased population of active receptor conformations both for rhodopsin (photoactivated and transducin-bound (Rho*−G t )>photoactivated (Rho*)>ground state (Rho)) and the serotonin type 4 (5-HT4) receptor (apo>inverse agonist bound)2324 (Fig.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The path of ACKR3 residues with agonist-induced increases in oxidation rates is in striking agreement with solvent networks identified in active states of both rhodopsin and opioid receptors (Fig. 8b)4143. Previous radiolytic footprinting studies of GPCRs have shown that higher oxidation rates of residues lining this path correlate with an increased population of active receptor conformations both for rhodopsin (photoactivated and transducin-bound (Rho*−G t )>photoactivated (Rho*)>ground state (Rho)) and the serotonin type 4 (5-HT4) receptor (apo>inverse agonist bound)2324 (Fig.…”
Section: Resultssupporting
confidence: 81%
“…Many of these residues are buried in the TM domain of the receptor and cannot possibly be exposed to bulk solvent; therefore, their changes in oxidation are due to rearrangement of structured water molecules within the TM domain. Such water molecules are consistently found in several 7TM receptors by X-ray crystallography or structure-based MS experiments233839, and their positions appear to be affected by receptor activation, leading to restructuring of water-mediated polar residue networks404142. The path of ACKR3 residues with agonist-induced increases in oxidation rates is in striking agreement with solvent networks identified in active states of both rhodopsin and opioid receptors (Fig.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…the reorientation of W265 6.48 is consistent with a conformational transition, and the increased solvent accessibility of the intracellular region with opening of a binding cleft to accommodate intracellular effectors (60, 108). Furthermore, the results corroborate the hypothesis of activation being mediated by an extensive water-mediated intramolecular polar network in GPCRs (8, 55). Taken together, these results suggest that although ACKR3 exclusively activates β-arrestin dependent pathways, its active conformation is similar to that of canonical GPCRs.…”
Section: Structural Basis Of Chemokine Receptor Interactions With Chesupporting
confidence: 83%
“…3e). Finally, R134 3.50 and L226 were identified as critical by the screen and likely represent G protein interaction hotspots as their coupling role is conserved across several GPCRs (8, 108) (Fig. 3f).…”
Section: Structural Basis Of Chemokine Receptor Interactions With Chementioning
confidence: 99%